21. Legal and Institutional Framework Analysis: Karelian, Veps, and Seto in Russia: Working Papers in European Language Diversity 21 - Fogelklou, Anders
The Legal and Institutional Framework Analyses represent the collected knowledge of the ELDIA-project in the field of law, politics and policies and of their institutional representations with regard to the languages studied in this research project. Each report examines one or two languages in their wider national and international context. The core scientific questions in the present law and policy studies are: What role is played by law in the use or non-use of different languages in different domains? What role is played by law in promoting or inhibiting language diversity as such? Finally, which factors related to legal and institutional matters influence language use, language maintenance and language diversity? Each study consists of three main parts: a) The overall legislative and institutional framework; b) Languages and minority policies in practice (a section which covers the discussions and the implementation, or non-implementation, of constitutional provisions, language legislation, education and media legislation) and c) an identification and analysis of the legal actors, i.e. persons, organisations, and public authorities engaged in the development, interpretation and monitoring (judicial and other) of the relevant legal frameworks. The law researchers involved in this part of the research have benefited greatly from the input of and interactions with the broad network of researchers represented in the project, and thus we are now even more convinced that contacts across scientific disciplines is a precondition for a deeper understanding of complex societal processes. The Legal and Institutional Framework Analyses shall form part of the background for the development of the comparative and interdisciplinary work that is currently taking place within the ELDIA-project. As all Working Papers published on the project website and within ELDIA, also these studies have been submitted to extensive project internal as well as external review under the supervision of Associate Professor, Jur. Dr., Sia ...